2022
DOI: 10.1371/journal.pone.0268591
|View full text |Cite
|
Sign up to set email alerts
|

Placental vascular remodeling in pregnant women with COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 has been causing the pandemic of coronavirus disease 2019 (COVID-19) that has so far resulted in over 450 million infections and six million deaths. This respiratory virus uses angiotensin-converting enzyme 2 as a receptor to enter host cells and affects various tissues in addition to the lungs. The present study reports that the placental arteries of women who gave birth to live full-term newborns while developing COVID-19 during pregnancy exhibit severe vascula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
2
8
0
2
Order By: Relevance
“…In addition to the morphological changes mentioned above in the placenta as a result of COVID-19, a study conducted last year found an abnormality in the umbilical cord of COVID-19 pregnancies to be high, whereby it attached to the margin of the placenta resulting in altered functioning and blood flow [ 82 ]. In addition, vascular remodelling in the arteries of the placenta in COVID-19 pregnancies have now been identified through histological examinations and documented [ 85 ]. Therefore, it can be speculated that in COVID-19 pregnancies the oxygen demand increases, however this demand is not met.…”
Section: The Effect Of Covid-19 On Pregnanciesmentioning
confidence: 99%
“…In addition to the morphological changes mentioned above in the placenta as a result of COVID-19, a study conducted last year found an abnormality in the umbilical cord of COVID-19 pregnancies to be high, whereby it attached to the margin of the placenta resulting in altered functioning and blood flow [ 82 ]. In addition, vascular remodelling in the arteries of the placenta in COVID-19 pregnancies have now been identified through histological examinations and documented [ 85 ]. Therefore, it can be speculated that in COVID-19 pregnancies the oxygen demand increases, however this demand is not met.…”
Section: The Effect Of Covid-19 On Pregnanciesmentioning
confidence: 99%
“…Pancreatic beta cells express KCNH2 , and loss-of-function KCNH2 variants are associated with hyperinsulinemia and diabetes ( 58 , 59 ). KCNH2 is also expressed in smooth muscle tissues, where it regulates contractile function ( 60 , 61 ), and is associated with vascular remodeling ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The placental arterial lumen area was found to be significantly smaller (5-fold) in SARS-CoV-2 patients than in the controls (p < 0.01). In addition, immunohistochemistry using the smooth muscle cell marker α-smooth muscle actin clearly indicated a dramatic increase in smooth muscle mass in the placental arteries of SARS-CoV-2 patients, with quantitatively thickened placental vessels [50]. Another recent case-control study reported significant pathological alterations in the placenta and umbilical cord [51].…”
Section: Route Of Sars-cov-2 During Pregnancy and Its Consequencesmentioning
confidence: 92%
“…Gychka et al [50] provided a morphometric and immunohistochemistry analysis of placental tissue. Interestingly, the authors observed significant remodeling of vessels in the placentas of SARS-CoV-2-positive women.…”
Section: Route Of Sars-cov-2 During Pregnancy and Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation